The Difference of Risk Factors Between Mild and Moderate-Severe Refractive Errors in Pediatric Patients at the Diponegoro National Hospital - Fitriani, Rizky; Nugroho, Trilaksana; Saubig, Arnila Novitasari (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Refractive errors are the leading cause of visual impairment and the second leading cause of blindness worldwide. The incidence of refractive errors in children in Indonesia and in the world is quite high. The incidence of refractive errors can be triggered by several risk factors, including genetics, age, gender, close-range activities, use of electronic devices, and outdoor activities. Objective: Knowing the difference in risk factors between mild and moderatesevere refractive errors in pediatric patients at the Diponegoro National Hospital.Methods: This type of research is an analytic observational study with a cross sectional approach. Data were taken using a consecutive sampling technique from questionnaires and medical records of pediatric patients in the 2018-2021 period. The research subjects were 57 people who met the inclusion and exclusion criteria. Data were analyzed by univariate and bivariate analysis using Chi-Square and Mann Whitney analysis. Results: The research subjects were dominated by the age of 16-18 years (63.2%), female gender (68.4%), types of myopia disorders (57.9%), and mild degrees (66.7%). The results of the Chi-Square analysis showed that there was a significant difference in reading distance (p=0.000), reading position (p=0.035), duration of use of electronic devices (p=0.031), and duration of outdoor activities (p=0.042) between mild and moderatesevere degrees. Conclusion: There are significant differences in reading distance, reading position, duration of use of electronic devices, and duration of outdoor activities between mild and moderate-severe refractive errors in pediatric patients at the Diponegoro National Hospital.